Review: Advances in Magnetic Biochar-Based Cellulase Immobilization Systems for Enhancing Hydrolysis Efficiency in Second-Generation Bioethanol - Nessi Rahmadani; Hadistya Suryadri; Rara Ayu Lestary; Rosmawati Sipayung (Program studi Teknik Kimia UNS, 2026)
Abstract: Second-generation bioethanol production utilizes abundant lignocellulosic biomass, such as agricultural residues and woody materials, without competing with food resources. Enzymatic hydrolysis of cellulose into glucose using cellulase is more environmentally friendly than conventional chemical methods; however, the practical application of free cellulase is often limited by low operational stability, sensitivity to temperature and pH fluctuations, and inhibition by compounds generated during biomass pretreatment. To address these challenges, enzyme immobilization on solid supports has been extensively investigated as an effective approach to enhance enzyme stability and enable repeated use. The incorporation of magnetic particles, typically Fe₃O₄, into biochar results in magnetic biochar, which enables rapid separation from the reaction medium using an external magnetic field and facilitates enzyme recovery and reuse. This review summarizes recent studies published between 2020 and 2025 on the application of magnetic biochar as a support for cellulase immobilization to improve the efficiency of lignocellulosic hydrolysis. Reported results demonstrate high enzyme loading capacities (up to approximately 484 mg g⁻¹ biochar), glucose yields exceeding 90%, and retention of more than 80% of enzymatic activity after 5–10 reuse cycles. Overall, magnetic biochar-based immobilization significantly enhances the thermal and pH stability of cellulase, contributing to a more efficient and economically viable saccharification process for second-generation bioethanol production.Keywords: Cellulase, enzyme immobilization, magnetic biochar